Establishment and application of a quadruple RT-qPCR method for simultaneous detection of porcine enteric coronaviruses - Ye, Caiwang; Xu, Jingru; Fan, Sisi; Chen, Fangting; Qiu, Shuqi; Pan, Huachun; Yang, Shumin; Li, Yuqi; Liao, Yuting; Lin, Weiye; Xiao, Xiaoziyi; Li, Xuejin; et al. (Frontiers in Veterinary Science, 2025)
IntroductionPorcine enteric coronaviruses (PECs) are a group of viruses that cause severe diarrhea in piglets, significantly impacting the pig industry and resulting in huge economic losses. Important PECs include porcine epidemic diarrhea virus (PEDV), porcine enteric alphacoronavirus (PEAV), porcine deltacoronavirus (PDCoV), and transmissible gastroenteritis virus (TGEV). These pathogens cause highly similar clinical symptoms and pathological changes in piglets. Therefore, it is necessary to develop a simultaneous detection method for the precise prevention and control of porcine diarrheal diseases.MethodsTo establish a rapid, simple, and accurate detection method for differential diagnosis on these four pathogens, this study designed specific primers and probes based on the conserved regions of the M gene of PEDV, PEAV, and PDCoV, and the N gene of TGEV. By optimizing the reaction conditions, a quadruple fluorescence real-time quantitative RT-PCR (RT-qPCR) method for simultaneous detection of the four porcine diarrhea viruses was developed.ResultsThis method demonstrated high specificity, with no cross-reactivity with other common porcine pathogens such as porcine reproductive and respiratory syndrome virus, porcine circovirus, classical swine fever virus, porcine rotavirus, and pseudorabies virus. The sensitivity was excellent, with the limit of detection of 100 copies/μL in multiplex real-time RT-qPCR assays and all correlation coefficients (R2) exceeding 0.99. Repeatability was also strong, with the coefficient of variation of the intra- and inter-assay repeatability tests ranging from 0.3% to 1.0%.When applied to 231 clinical samples from Fujian province, the multiplex RT-qPCR method identified PEDV as the predominant pathogen, and often in co-infections. These results were 100% consistent with those from the commercial RT-qPCR kits, demonstrating the high accuracy of the developed method.DiscussionIn summary, this study established a specific, sensitive, and accurate multiplex RT-qPCR assay for the simultaneous detection of PEDV, PEAV, TGEV, and PDCoV, providing a valuable tool for the monitoring and differential diagnosis of these four PECs.